Siderosis bulbi as a consequence of a missed intraocular foreign body. (23rd January 2014) - Lapira, Matthew; Karl, David; Murgatroyd, Helen
Abstract : We present a case of a 56-year-old man who suffered an injury to his right eye in June 2012. He presented to an emergency department, however, the presence of a penetrating injury and an intraocular foreign body was not identified. A year later he was referred to the ophthalmology department due to reduced vision and change of iris colour in the same eye. Examination revealed clinical signs consistent with a previous penetrating injury and a retained ferrous intraocular foreign body.